Using Songs in English Language Teaching - Susana Teopilus (Widya Mandala Surabaya Catholic University, 2009)
Abstract. In ELT classes, for young learners or adult learners, songs can be used to set a context of a lesson (grammar, vocabulary, pronunciation, reading, listening, writing, and speaking) as they can be incorporated to all language skills and components. Attempting to encourage English teachers to occasionally use songs in their classes, this paper starts by showing the reasons why it is beneficial to use songs in ELT classrooms, continued by the guideline to select suitable songs for ELT and some activities of using songs in ELT classroom. Two models of using songs in ELT are also presented: one model for young learners’ class and one for adults’ class.